Nursing Home Use by Dual-Eligible Beneficiaries in the Last Year of Life - Korbin Liu; Douglas Wissoker; Althea Swett (SAGE Publishing, 2007)
Research on health care at the end of life has focused on Medicare-financed acute care services. Much less information has been available on nursing home use in the last year of life, particularly for individuals who are dually eligible for Medicare and Medicaid. We used Medicare and Medicaid enrollment and claims data to examine nursing home admissions, odds of dying in nursing homes versus hospitals or the community, and variations in Medicare and Medicaid service use and costs by place of death. We found that, in the last year of life, 75% of dual-eligible people use nursing home care, increasing age is associated with greater likelihood of dying in nursing homes, and dual-eligible people who die in hospitals have notably higher costs than other beneficiaries.